IUCN Global Ecosystem Typology 2.0 - Keith, David A.; Ferrer-Paris, Jose R.; Nicholson, Emily; Kingsford, Richard (IUCN, 2020)
Ecosystems are critically important components of Earth’s biological diversity and as the natural capital that sustains human life and well-being. Yet all of the world’s ecosystems show hallmarks of human influence, and many are under acute risks of collapse, with consequences for habitats of species, genetic diversity, ecosystem services, sustainable development and human well-being. The IUCN Global Ecosystem Typology is a hierarchical classification system that, in its upper levels, defines ecosystems by their convergent ecological functions and, in its lower levels, distinguishes ecosystems with contrasting assemblages of species engaged in those functions. This report describes the three upper levels of the hierarchy, which provide a framework for understanding and comparing the key ecological traits of functionally different ecosystems and their drivers. An understanding of these traits and drivers is essential to support ecosystem management.